Development of Learning Media Based on Interactive Presentation Using Ahaslides Software on Choux Paste Material at Telkom Tourism Vocational School - Muhammad Resnu Wildan Imani; Atat Siti Nurani; Sri Subekti (Media Pendidikan Gizi dan Kuliner, 2023)
In learning choux paste in class xi-tb 4 at Telkom Bandung Tourism Vocational School, it was found that 77% of students did not understand the choux paste material. Students must understand the theory of making choux paste because in practice it is quite difficult to make. This has become the author's attention to developing interactive presentation-based learning media using AhaSlides software on choux paste material at Telkom Bandung Tourism Vocational School.The research objectives are (1) planning the development of interactive presentation-based learning media using AhaSlides software, (2) creating interactive presentation-based learning media using AhaSlides software, (3) carrying out validation tests on interactive presentation-based learning media using AhaSlides software. This research uses the first level Research and Development (RD) method, with a descriptive qualitative approach. The research results stated that (1) planning the development of interactive presentation-based learning media using AhaSlides software, with stages of finding potential problems, literature study, product design. (2) create interactive presentation-based learning media with the stages of creating an account on the Ahaslides software, creating files on the AhaSlides software, creating interactive presentations. (3) Carrying out validation tests on material, language and media, with a statement that they are suitable for use.